Synthesis and Crystal Structure of 3-(1,1,1,3,3,3-Hexamethyldisilazan- 2-yl)-1-phenyl-1H-indene-2-carbonitrile - LIU, YONG-JUN; ZHONG, HUA; QI, YAN; ZHANG, SHU-SHENG (Asian Journal of Chemistry, 2010)
The crystal structure of 3-(1,1,1,3,3,3-hexamethyldisilazan- 2-yl)-1-phenyl-1H-indene-2-carbonitrile has been determined by X-ray diffraction method. The crystal is orthorhombic with space group P212121, a = 8.6317(2) Å, b = 14.8822(3) Å, c = 17.5719(3) Å, V = 2257.26(8) Å3, Z = 4, and R1 = 0.047, wR2 = 0.129 for 2016 observed reflections (I > 2.00σ(I)). The mean plane of indene is almost perpendicular to the phenyl ring attached at chloro atom, the dihedral angling being 84.4(1)º. In the crystal packing, the molecules are stabilized by C-H…π and C-H…N interactions.